Meeting of the Atlantic & Pacific, The Kiss of the Oceans (I. L. Maduro Jr.)
On recto: Canal Statistics Length 40 miles Channel width on top 500 to 1000ft channel width on bottom, 300-650 ft Time of passage Through Canal 10 hours Through Locks 3 hours. Gatun Dam Length of crest 8000ft Extreme width 2600 ft. Locks At Gatun 3 double sets, At Pedro Miguel 1 double set, At Miraflores 2 double sets Average lift 32 ft. Length 1000 Width 110 ft Culebra Cut Length 9 miles Total number of men employed 40,000 Estimated total cost 375,000,000 Area of Canal Zone 448 Sq. Miles